Valuation accurancy in South Africa - Mabuza, Sandile Innocent (My University, 2017)
Background The perception of inconsistent and uncertain valuations has been the subject of debate worldwide. However, it is a phenomenon that has gone largely ignored in South Africa. The effect of unreliable valuations cannot be overstated, as all lending and investment decisions are based on valuation estimates. Objectives This study seeks to investigate the level of valuation accuracy in South Africa by comparing mortgage valuation estimates done prior to finance of the properties against their actual realised transaction prices. Methods and Results Valuers from four financial institutions as well as from external valuation firms were randomly chosen to participate in a questionnaire and in addition 32,826 properties which were valued and sold between January to December 2016 were also analysed. The valuation estimates and actual transaction prices were collected in an Excel file. While data from the banks and valuers was collected and analysed using Qualtrics. Data was analysed using R software version 3.3.3 to come up with descriptive and inference statistics. The result of the analysis showed that the level of valuation accuracy for the properties in South Africa used in the study is high (2.03%), which shows a very high level of accuracy compared to the adopted benchmark of 10%. The accuracy level across the three provinces in our study namely Gauteng, KwaZulu-Natal and Western Cape is 2.23%, 1.93% and 1.58% respectively, indicating that valuation accuracy is higher in Western Cape than Gauteng and KwaZulu-Natal Conclusion The study revealed that valuation estimates were good proxies of the market value (actual realised sale prices). Based on the 10% acceptable margin of error benchmark adopted by this study it shows that valuers in South Africa are indeed accurate in as far as estimating residential cost values. Based on the 2.03% level of accuracy obtained in this study, we recommend that valuation stakeholders adopt 5% maximum margin of error between valuation estimates and actual realised prices.
Thesis is submitted in partial fulfilment for the degree of M.Sc. Building (Property Development and Marketing) to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Real estate investment--South Africa; Real estate development--South Africa; Real estate business--South Africa